Brain caspase-3 and intestinal FABP responses in preterm and term rats submitted to birth asphyxia - Figueira,R.L. (2016)
Neonatal asphyxia can cause irreversible injury of multiple organs resulting in hypoxic-ischemic encephalopathy and necrotizing enterocolitis (NEC). This injury is dependent on time, severity, and gestational age, once the preterm babies need ventilator support. Our aim was to assess the different brain and intestinal effects of ischemia and reperfusion in neonate rats after birth anoxia and mechanical ventilation. Preterm and term neonates were divided into 8 subgroups (n=12/group): 1) preterm control (PTC), 2) preterm ventilated (PTV), 3) preterm asphyxiated (PTA), 4) preterm asphyxiated and ventilated (PTAV), 5) term control (TC), 6) term ventilated (TV), 7) term asphyxiated (TA), and 8) term asphyxiated and ventilated (TAV). We measured body, brain, and intestine weights and respective ratios [(BW), (BrW), (IW), (BrW/BW) and (IW/BW)]. Histology analysis and damage grading were performed in the brain (cortex/hippocampus) and intestine (jejunum/ileum) tissues, as well as immunohistochemistry analysis for caspase-3 and intestinal fatty acid-binding protein (I-FABP). IW was lower in the TA than in the other terms (P<0.05), and the IW/BW ratio was lower in the TA than in the TAV (P<0.005). PTA, PTAV and TA presented high levels of brain damage. In histological intestinal analysis, PTAV and TAV had higher scores than the other groups. Caspase-3 was higher in PTAV (cortex) and TA (cortex/hippocampus) (P<0.005). I-FABP was higher in PTAV (P<0.005) and TA (ileum) (P<0.05). I-FABP expression was increased in PTAV subgroup (P<0.0001). Brain and intestinal responses in neonatal rats caused by neonatal asphyxia, with or without mechanical ventilation, varied with gestational age, with increased expression of caspase-3 and I-FABP biomarkers.